A new definition of the fuzzy set - Piegat, Andrzej (Zielona Góra: Uniwersytet Zielonogórski)
The present fuzzy arithmetic based on Zadeh's possibilistic extension principle and on the classic definition of a fuzzy set has many essential drawbacks. Therefore its application to the solution of practical tasks is limited. In the paper a new definition of the fuzzy set is presented. The definition allows for a considerable fuzziness decrease in the number of arithmetic operations in comparison with the results produced by the present fuzzy arithmetic.
Keywords: fuzzy set theory; fuzzy arithmetic; possibility